IMPLEMENTATION OF REFLECTIVE ASSIGNMENTS IN LANGUAGE TEACHING AND ASSESSMENT (Web of Teachers: Inderscience Research, 2025)
This article explores the integration of reflective assignments in language teaching and assessment practices. It emphasizes the importance of reflection as a tool for enhancing students' critical thinking and self-awareness in language learning. The author discusses various types of reflective assignments, such as critical reviews, reflective writings, essays, and peer assessments, highlighting their effectiveness in fostering deeper understanding and engagement with the language. Through case studies and practical examples, the article illustrates how reflective practices can improve not only language proficiency but also learners' ability to evaluate their own progress and learning strategies. The findings suggest that incorporating reflective assignments can lead to more meaningful learning experiences and better outcomes in language education.